2021
DOI: 10.3389/fpubh.2021.778863
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Pharmacists in Treating COVID-19 Patients? The Experiences and Expectations of Front Line Medical Staff

Abstract: Aims: The study aimed to understand the role and the core values of pharmacists and the professional expectations of medical staff for pharmacists in treating COVID-19 patients from the perspectives of the frontline medical staff. The findings help to understand and provide a reference for the career growth path of future pharmacists.Methods: A phenomenological method was used to conduct in-depth interviews with frontline medical staff working in isolation wards during COVID-19. The interview data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The value of pharmacist-led team care in pharmacotherapies has been demonstrated in numerous studies ( Yamamoto et al, 2018 ; Escudero-Vilaplana et al, 2020 ; Satsuma et al, 2020 ; Ji et al, 2021 ; Jia et al, 2021 ; Marzal-Alfaro et al, 2021 ; Miura et al, 2021 ; Xu et al, 2021 ). The results of this study revealed that pharmacist-urologist collaborative management can also improve care for patients with CRPC receiving enzalutamide in an ambulatory care setting.…”
Section: Discussionmentioning
confidence: 99%
“…The value of pharmacist-led team care in pharmacotherapies has been demonstrated in numerous studies ( Yamamoto et al, 2018 ; Escudero-Vilaplana et al, 2020 ; Satsuma et al, 2020 ; Ji et al, 2021 ; Jia et al, 2021 ; Marzal-Alfaro et al, 2021 ; Miura et al, 2021 ; Xu et al, 2021 ). The results of this study revealed that pharmacist-urologist collaborative management can also improve care for patients with CRPC receiving enzalutamide in an ambulatory care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists also helped by taking part in inpatient rounds. Pharmacists within the medical setup assumed an essential role in identifying drug interactions and reactions, providing consultation and drug information, as well as ensuring the supply of drugs that are not stocked routinely (Jia et al, 2021). Their roles were vital in ensuring that patients access adequate medication to fight against the negative health effects of the coronavirus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a meta-analysis reported an increased prevalence of Multi-Drug Resistant Organisms (MDROs) in COVID-19 wards [ 12 ], as well as an increased prevalence of QTc prolongation in COVID-19 patients secondary to unjustified use of hydroxychloroquine/chloroquine therapy or in cases of drug-drug interactions [ 13 , 14 ]. For the past 2 years, much literature has documented the general roles pharmacists are playing in the ongoing COVID-19 pandemic [ 15 , 16 ]. Nevertheless, AMS- related interventions by pharmacists and observed outcomes have not been the focus of those articles.…”
Section: Introductionmentioning
confidence: 99%